Improvement of submerged culture conditions to produce colorants by Penicillium purpurogenum - Santos-Ebinuma, Valeria Carvalho [UNESP]; Roberto, Ines Conceição; Simas Teixeira, Maria Francisca; Pessoa, Adalberto (Soc Brasileira Microbiologia, 2014)
Safety issues related to the employment of synthetic colorants in different industrial segments have increased the interest in the production of colorants from natural sources, such as microorganisms. Improved cultivation technologies have allowed the use of microorganisms as an alternative source of natural colorants. The objective of this work was to evaluate the influence of some factors on natural colorants production by a recently isolated from Amazon Forest, Penicillium purpurogenum DPUA 1275 employing statistical tools. To this purpose the following variables: orbital stirring speed, pH, temperature, sucrose and yeast extract concentrations and incubation time were studied through two fractional factorial, one full factorial and a central composite factorial designs. The regression analysis pointed out that sucrose and yeast extract concentrations were the variables that influenced more in colorants production. Under the best conditions (yeast extract concentration around 10 g/L and sucrose concentration of 50 g/L) an increase of 10, 33 and 23% respectively to yellow, orange and red colorants absorbance was achieved. These results show that P. purpurogenum is an alternative colorants producer and the production of these biocompounds can be improved employing statistical tool.
Keywords: natural colorants; filamentous fungi; optimization; submerged culture